Efektivitas Penggunaan Media Interaktif Wizer.Me Terhadap Mata Pelajaran IPA Pada Siswa Kelas XI SMA - Idyawati, Indah; Nurdin; Nasir (Jurnal Pendidikan dan Pembelajaran, 2022)
Research on the Effectiveness of using wizer.me interactive media on science subjects in class XI IPA II students at SMA Negeri 5 Bantaeng. Aims to determine the effectiveness of the use of wizer.me Interactive media in science subjects. This research is a type of quantitative research using experimental methods and the media used in this research, namely wizer.me. The sample is class XI IPA II students. The instruments in this study provide pre- and post-tests on the sample. Data collection techniques used are observation, tests, and documentation. Data analysis techniques are descriptive statistical analysis and inferential statistical analysis. Comparison of learning outcomes categories, and comparison of completeness levels has proven an increase in student learning outcomes in class XI IPA II at SMA Negeri 5 Bantaeng. It can be seen that student learning outcomes through descriptive statistical analysis before using wizer.me interactive media, the average student score is still below the mark KKM and after using wizer.me interactive media the average student score increased. He obtained that the posttest result value was 80.5, which was greater than the pretest result value, which was 61.75. Furthermore, based on the results of inferential statistical analysis using the t test formula, it is known that the t count obtained is 13.708, at a significant level = 0.05 or 5%, the t table is 1.740. So tCount > tTable or 13.708>1.740 thus H0 is rejected and H1 is accepted. From the results of this study it can be concluded that by using wizer.me interactive media it has been effectively used in learning science for class XI IPA II at SMA Negeri 5 Bantaeng.